the inverse of the exponential function, given as f(x)=logax
The inverse of the exponential function f(x) = a^x, where a is a positive constant greater than 1, is the logarithmic function g(x) = log_a(x)
The inverse of the exponential function f(x) = a^x, where a is a positive constant greater than 1, is the logarithmic function g(x) = log_a(x).
To understand how these functions are inverses of each other, let’s consider an example. Let’s assume a = 2. For the exponential function f(x) = 2^x, if we plug in x = 2, we get f(2) = 2^2 = 4. This tells us that when we raise 2 to the power of 2, we get 4.
Now, if we want to find the inverse of this function, we switch the x and y variables. So, instead of y = 2^x, we have x = 2^y. Solving for y in terms of x, we take the logarithm of both sides with base 2. This gives us log_2(x) = y. Here, x is the input and y is the output of the inverse function.
Therefore, the inverse of f(x) = 2^x is g(x) = log_2(x). If we plug in x = 4 into the inverse function, we get g(4) = log_2(4) = 2. This tells us that if we raise 2 to the power of 2, we get 4, just like we observed when evaluating f(2) = 4.
In summary, the inverse of an exponential function of the form f(x) = a^x is the logarithmic function of the same base, given by g(x) = log_a(x). This applies to any positive constant a greater than 1.
More Answers:
How to Find the Derivative of the Cotangent Function Using the Quotient Rule and Trigonometric IdentitiesExplaining the Power Rule | Differentiating Functions of the Form f(x) = x^n
Understanding Logarithms with Base 10 | Simplifying Complex Calculations and Standard Representation in Science and Engineering